Audiologist-guided internet-based cognitive behavior therapy for adults with tinnitus in the United Kingdom: a randomized controlled trial - Beukes, Eldre W.; Baguley, David; Allen, Peter M.; Manchaiah, Vinaya; Andersson, Gerhard (Wolters Kluwer, 2017)
Objectives: Specialist tinnitus services are in high demand as a result of the negative effect tinnitus may have on quality of life. Additional clinically and cost-effective tinnitus management routes are needed. One potential route is providing Cognitive Behavioural Therapy for tinnitus via the Internet (iCBT). This study aimed to determine the efficacy of guided iCBT, using audiological support, on tinnitus distress and tinnitus-related comorbidities, in the United Kingdom. A further aim was to establish the stability of intervention effects 2-months postintervention. The hypothesis was that iCBT for tinnitus would be more effective at reducing tinnitus distress than weekly monitoring.